Exosomal MicroRNA-374b-5p From Tubular Epithelial Cells Promoted M1 Macrophages Activation and Worsened Renal Ischemia/Reperfusion Injury - Ding, Chenguang; Zheng, Jin; Wang, Bo; Li, Yang; Xiang, Heli; Dou, Meng; Qiao, Yuxi; Tian, Puxun; Ding, Xiaoming; Xue, Wujun (Frontiers in Cell and Developmental Biology, 2020)
Abbreviation: TECs, tubular epithelial cells; RIRI, renal ischemia/reperfusion injury; miRNAs, microRNAs; IRI, ischemia and reperfusion injury; AKI, acute kidney injury; MCP-1, monocyte chemoattractant protein-1; TNF-α, tumor necrosis factor-α; IL-1β, interleukin-1β; SCr, serum creatinine; BUN, blood urea nitrogen; PAS, periodic acid-Schiff; SOCS-1, suppressor of cytokine signaling-1; DMEM, Dulbecco's Modified Eagle Medium; FBS, fetal bovine serum; TEM, transmission electron microscope; DAPI, 4, 6-diamidino-2-phenylindole; iNOS, inducible nitric oxide synthase; i.p., intraperitoneal injection; OE, overexpression; KD, knockdown; WT, wildtype; MUT, mutant; Hypo, hypoxia; Exo, exosome; ctrl, inhibitor control. we demonstrated global microRNAs (miRNAs) expression profiling of renal exosomes, and miR-374b-5p was most upregulated in these exosomes in vivo.Inhibition of miR-374b-5p in the mice upon RIR operation would alleviate the kidney injury via decreasing the production of pro-inflammatory cytokines and suppressing the macrophage activation. Similar results were also identified in the hypoxia-induced cell model where exosomal miR-374b-5p was dramatically upregulated. Uptake of exosomes derived from the hypoxic TECs by microphage would trigger phenotype polarization via transferring miR-374b-5p. Besides, we confirmed that miR-374b-5p could directly bind to SOCS-1 using a dual-luciferase assay. Importantly, when we injected the miR-374b-5p-enriched exosomes into mice, a high-level inflammatory response and M1 macrophage activation were performed. Taken together, our studies demonstrated that exosomal miR-374b-5p played an important role in the communication between injured-TECs and macrophages, resulting in the M1 macrophage activation during RIRI. The blockage of the release of such exosomes may serve as a new therapeutic strategy for RIRI.